2019
DOI: 10.1242/jcs.230672
|View full text |Cite
|
Sign up to set email alerts
|

The golgin PpImh1 mediates reversible cisternal stacking in the Golgi of the budding yeast Pichia pastoris

Abstract: The adhesive force for cisternal stacking of Golgi needs to be reversibleto be initiated and undone in a continuous cycle to keep up with the cisternal maturation. Microscopic evidence in support of such a reversible nature of stacking, in the form of 'TGN peeling,' has been reported in various species, suggesting a potential evolutionarily conserved mechanism. However, knowledge of such mechanism has remained sketchy. Here, we have explored this issue in the budding yeast Pichia pastoris which harbors stacked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(75 reference statements)
1
7
0
Order By: Relevance
“…This fragment was digested with EcoRI and SphI and subcloned into pIB1 ( Sears et al, 1998 ) cut with the same enzymes. BamHI and NotI sites were introduced by site-directed mutagenesis immediately after the start codon, and a cassette encoding msGFP was excised with BamHI and NotI and inserted ( Jain et al, 2019 ). This plasmid was linearized with StuI and integrated at the HIS4 locus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fragment was digested with EcoRI and SphI and subcloned into pIB1 ( Sears et al, 1998 ) cut with the same enzymes. BamHI and NotI sites were introduced by site-directed mutagenesis immediately after the start codon, and a cassette encoding msGFP was excised with BamHI and NotI and inserted ( Jain et al, 2019 ). This plasmid was linearized with StuI and integrated at the HIS4 locus.…”
Section: Methodsmentioning
confidence: 99%
“…A pUC19-ARG4 derivative containing a 3′ portion of the P. pastoris SEC7 coding sequence plus a downstream region ( Bevis et al, 2002 ) was modified by inserting a 6xDsRed.M1 cassette in place of the stop codon ( Losev et al, 2006 ). This plasmid was linearized with XmnI and integrated at the SEC7 locus (( Jain et al, 2018 ); Jain et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…To observe the structural changes in the Golgi it was necessary to generate a visualization method that could indicate whether the Golgi remained stacked or was disrupted. Previous research has shown that it is possible to use two different fluorescent proteins fused to early and late Golgi markers 16,20,22,23 where co‐localization indicates a stacked Golgi. In order to generate such a system, we selected Vrg4p (PAS_chr3_0916), used by Connerly et al, 20 Losev et al, 23 and Jain et al 22 as the early Golgi marker, and fused this to a superfolder GFP (sfGFP).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that it is possible to use two different fluorescent proteins fused to early and late Golgi markers 16,20,22,23 where co‐localization indicates a stacked Golgi. In order to generate such a system, we selected Vrg4p (PAS_chr3_0916), used by Connerly et al, 20 Losev et al, 23 and Jain et al 22 as the early Golgi marker, and fused this to a superfolder GFP (sfGFP). Although previous research had used Sec7p (PAS_chr1‐4_0667) as the late Golgi marker, 24 we were interested in observing the impact of this gene on the structural organization of the Golgi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation